1981
DOI: 10.1152/jappl.1981.51.3.654
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm electrical activity during negative lower torso pressure in quadriplegic men

Abstract: We recorded the diaphragm electromyogram (EMG) of quadriplegic men before and during exposure of the lower torso to continuous negative pressure, which caused shortening of the inspiratory muscles by expanding the respiratory system by one tidal volume. The moving-time-averaged diaphragm EMG was larger during expansion of the respiratory system. When we repeated the experiment with subjects who breathed through a mouthpiece, we found qualitatively similar EMG changes and little or no change in tidal volume or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Only when the diaphragm is stretched beyond the optimal length, and is therefore placed on the descending limb of its force-length curve, is its electrical activity increased [29]. The same happens when the diaphragm gets shorter and is therefore placed in a more disadvantageous position from a mechanical point of view [1,13]. These studies imply that the drive to the inspiratory muscles is adjusted for shifts in position along the muscle lengthtension curve to provide stability in pulmonary ventilation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Only when the diaphragm is stretched beyond the optimal length, and is therefore placed on the descending limb of its force-length curve, is its electrical activity increased [29]. The same happens when the diaphragm gets shorter and is therefore placed in a more disadvantageous position from a mechanical point of view [1,13]. These studies imply that the drive to the inspiratory muscles is adjusted for shifts in position along the muscle lengthtension curve to provide stability in pulmonary ventilation.…”
Section: Discussionmentioning
confidence: 97%
“…If the increased EMGdi activity in the filled state simply represents a reflex mechanism caused by the instillation of dialysate, the EMGdi/Pdi ratio will then spuriously underestimate the diaphragmatic efficiency. Several animal and human studies have shown, however, that the efferent drive to the diaphragm is very well adjusted to account for changes in diaphragmatic mechanical efficiency [1,6,13,27]. Conditions that lead to an increased diaphragmatic operating length (the diaphragm is placed in a more advantageous position from a mechanical point of view) are associated with a reduced neural activation of the diaphragm [6,27].…”
Section: Discussionmentioning
confidence: 99%
“…Several animal and human studies have shown that the efferent drive to the diaphragm is very well adjusted to account for changes in diaphragmatic mechanical efficiency [23][24][25][26]. The conditions that lead to an increased diaphragmatic operating length (the diaphragm is placed in a mechanically more advantageous position) are associated with a reduced neural activation of the diaphragm [24,26].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous work has shown EMG activity from transmandibular electrodes to be qualitatively similar to signals from genioglossus intramuscular electrodes,21 and surface diaphragmatic EMG recordings are qualitatively similar to signals obtained from oesophageal electrodes even during changes in lung volume. 22 In patients with COPD it has been shown that the surface diaphragmatic EMG correlates well with transdiaphragmatic pressure. 7 We found no evidence of abdominal muscle activity during sleep, but cutaneous electrodes are probably less sensitive for detection of expiratory activity as recent work has shown that the most frequently active expiratory muscle in awake subjects with COPD is transversus abdominis, which is the least accessible to surface recording.…”
Section: Discussionmentioning
confidence: 99%
“…Others 22 In patients with COPD it has been shown that the surface diaphragmatic EMG correlates well with transdiaphragmatic pressure. 7 We found no evidence of abdominal muscle activity during sleep, but cutaneous electrodes are probably less sensitive for detection of expiratory activity as recent work has shown that the most frequently active expiratory muscle in awake subjects with COPD is transversus abdominis, which is the least accessible to surface recording.…”
Section: Resultsmentioning
confidence: 99%